Invertebrate Colonization During Leaf Decomposition of Eichhornia azurea (Swartz) Kunth (Commelinales: Pontoderiaceae) and Salvinia auriculata Aubl. (Salvinales: Salvinaceae) in a Neotropical Lentic System - da Silveira, Lidimara Souza; Martins, Renato Tavares; Alves, Roberto da Gama (EntomoBrasilis, 2016)
Abstract. The decomposition of macrophytes is an essential process for cycling of carbon and nutrients, and it is source of organic matter for invertebrates in lakes. We evaluated the colonization by aquatic invertebrates in decomposing leaves of two species of macrophytes in a Neotropical lentic system. The experiment was conducted from November 2007 to February 2008, with the use of 54 litter bags (Eichhornia azurea (Swartz): n = 27 and Salvinia auriculata Aubl.: n= 27), each containing 10 g of dry leaves. Three bags of each species were retrieved after 2, 4, 8, 12, 24, 36, 48, 60 and 72 days of incubation. The remaining leaf mass of the two macrophytes species tended to decrease with time, although at different rates. The decomposition of E. azurea and S. auriculata leaves were classified as rapid and intermediate, respectively. In general, during the experiment carbon: nitrogen ratio declined in E. azurea and increased in S. auriculata, and presented difference among the days of the experiment and between the macrophyte species. In E. azurea mass loss was negatively correlated with carbon: nitrogen ratio of the leaves, but the same pattern was not observed for the S. auriculata leaves. The composition and richness of invertebrates differed among days, but not between macrophytes species. We concluded that the succession process along the detritus chain was more important in structuring the invertebrate community than the variation in the nutritional quality of the leaf litter for these two species of macrophytes. Colonização por Invertebrados Durante a Decomposição foliar de Eichhornia azurea (Swartz) Kunth (Commelinales: Pontoderiaceae) e Salvinia auriculata Aubl. (Salvinales: Salvinaceae) em um Sistema Lêntico Neotropical Resumo. A decomposição de macrófitas é um processo essencial para ciclagem de carbono e nutrientes, e é fonte de matéria orgânica para invertebrados em lagos. Avaliamos a colonização por invertebrados aquáticos em folhas em decomposição de duas espécies de macrófitas em um sistema lêntico Neotropical. O experimento foi conduzido entre novembro de 2007 e fevereiro de 2008, com a utilização de 54 sacos de detrito (Eichhornia azurea (Swartz): n = 27 e Salvinia auriculata Aubl.: n = 27), cada um contendo 10 g de folhas secas. Três sacos de cada espécie foram recuperados após 2, 4, 8, 12, 24, 36, 48, 60 e 72 dias de incubação. A massa remanescente de folha das duas espécies de macrófitas tendeu a diminuir com o tempo, embora a velocidades diferentes. A decomposição de folhas de E. azurea e S. auriculata foram classificadas como rápida e intermédia, respectivamente. Em geral, durante o experimento a razão carbono: nitrogênio diminuiu em E. azurea e aumentou em S. auriculata, e apresentou diferença entre os dias de experimento e entre as espécies de macrófitas. Em E. azurea perda de massa foi negativamente correlacionada com a razão de carbono: nitrogênio das folhas, mas o mesmo padrão não foi observado para as folhas de S. auriculata. A composição e riqueza de invertebrados diferiram entre os dias, mas não entre espécies de macrófitas. Concluímos que o processo de sucessão ao longo da cadeia de detritos foi mais importante na estruturação da comunidade de invertebrados do que a variação na qualidade nutricional do detrito de folha para estas duas espécies de macrófitas.